2023
DOI: 10.3390/su151310501
|View full text |Cite
|
Sign up to set email alerts
|

Board Gender Diversity and Banks Profitability for Business Viability: Evidence from Serbia

Abstract: As an important topic in the field of corporate governance, the influence of the board of directors’ characteristics on the profitability of corporations is examined here. This paper examines the influence of the board of directors’ and chief executive officers’ (CEO) characteristics on the profitability of banks in Serbia. In this study, the characteristics of boards of directors were examined in terms of size and the participation of women, and the characteristics of CEOs were examined similarly in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…After doing a hypothesis test, it can be said that the hypothesis that states that board diversity has no bearing on return on assets (ROA) is rejected. This aligns with earlier research by Milojević et al (2023), which found that Return on Assets (ROA) is not significantly affected by Board Diversity. The study also found that women are underrepresented on bank management boards, making it challenging to evaluate and ascertain their contribution to financial effectiveness and performance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After doing a hypothesis test, it can be said that the hypothesis that states that board diversity has no bearing on return on assets (ROA) is rejected. This aligns with earlier research by Milojević et al (2023), which found that Return on Assets (ROA) is not significantly affected by Board Diversity. The study also found that women are underrepresented on bank management boards, making it challenging to evaluate and ascertain their contribution to financial effectiveness and performance.…”
Section: Discussionsupporting
confidence: 91%
“…An increasing number of studies also demonstrate the beneficial effects of gender diversity on a board and on an organization's financial and operational performance. According to research on board diversity conducted by Milojević et al (2023), the presence of women on the board of directors did not significantly affect bank profitability. Board gender diversity, according to Bogdan et al (2023), has shown the beneficial impact of female leader attributes on business development plans and, as a result, on firm success.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The question of economic growth is inseparable from the consideration of renewable energy consumption [40]. The findings of Stamenović [41] indicate that the balanced activities of social value creation and commercialization of effects are the perception of the sustainability strategy of academics and management for the evaluation of business viability, and it is important to observe the structure of the board of directors according to various criteria [42].…”
Section: Literature Reviewmentioning
confidence: 99%